Analyzing the security of e-Health data based on a hybrid federated learning model - Shafin, Md. Mehtabul Islam; Akhter, Sabrin; Hasan, Mohammad Shafkat; Nasimuzzaman, Md.; Prithul, Tamzeedur Rahman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.